Matthew C. Brown and John C. Brown papers - Brown, Matthew C.; Brown, Charles Matthew; Brown, John C., -1863.
Correspondence and military records pertaining to service in the 23rd Iowa Infantry Regiment. Chiefly letters from Matthew C. and John C. Brown to their parents in Oswego, N.Y., as well as records regarding clothing, camp equipment, and weapons. Also includes a history of the regiment by Charles Matthew Brown, Jr., and transcripts of the correspondence.
Matthew C. Brown, carpenter and Union officer; and John C. Brown, newspaper editor and Union officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brown family -- Correspondence; United States. -- Army. -- Iowa Infantry Regiment, 23rd (1862-1865); United States -- History -- Civil War, 1861-1865.; Army officers